Realization of Green Engineering at ETUT - Serdar Gedayev; Yslam Orazov (Journal of Sustainability Perspectives, 2023)
Despite being one of the young universities in the country, Oguz han Engineering and technology university of Turkmenistan (ETUT) aims to integrate all sustainable development goals in all aspects of its education and research programs within the scope of “Green Engineering." To increase the awareness and recognition of green engineering in our university, community, country, and world, we are developing sustainable projects such as the production of green hydrogen through solar panels, conversion of plastic waste into liquid fuel, bioethanol production from cotton stalks, sorting of solid wastes with a novel waste separator, production of synthetic fibers, clonal propagation of local plants, and obtaining of degradable bioplastics. This paper will explain these projects in detail accordingly. Realization and implementation of these projects into our society will contribute to applying sustainable development goals in the energy, climate change, and waste management areas of campus sustainability.